2020
DOI: 10.3390/molecules25092049
|View full text |Cite
|
Sign up to set email alerts
|

Two Annulated Azaheterocyclic Cores Readily Available from a Single Tetrahydroisoquinolonic Castagnoli–Cushman Precursor

Abstract: A novel approach to indolo[3,2-c]isoquinoline and dibenzo[c,h][1,6]naphthyridine tetracyclic systems was discovered based on switchable reduction of 2-methoxy-3-(2-nitrophenyl)-1-oxo-1,2,3,4-tetrahydroisoquinoline-4-carboxylic acid prepared via Castagnoli–Cushman reaction. Reduction with ammonium formate resulted in the expected selective transformation of the nitro group (thus providing access to substituted dibenzo[c,h][1,6]naphthyridine via cyclization and dehydrogenation). However, attempted reduction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The key heteropolycyclic intermediate (10a) was prepared following the procedure established in a previous study, 35 and the method for synthesizing the other central scaffolds (10b−10g) was similar to that for synthesizing compound 10a. 9-Methoxy-6,11-dihydro-5H-indolo [3,2-c] 6.92 (dd, J = 8.8, 2.5 Hz, 1H), 4.04 (q, J = 6.9 Hz, 2H), 1.38 (t, J = 6.9 Hz, 3H).…”
Section: Synthesis Of 10a−10gmentioning
confidence: 99%
See 1 more Smart Citation
“…The key heteropolycyclic intermediate (10a) was prepared following the procedure established in a previous study, 35 and the method for synthesizing the other central scaffolds (10b−10g) was similar to that for synthesizing compound 10a. 9-Methoxy-6,11-dihydro-5H-indolo [3,2-c] 6.92 (dd, J = 8.8, 2.5 Hz, 1H), 4.04 (q, J = 6.9 Hz, 2H), 1.38 (t, J = 6.9 Hz, 3H).…”
Section: Synthesis Of 10a−10gmentioning
confidence: 99%
“…The contrast of the antiproliferative activities of compounds 25−35 revealed that the antitumor activities of compounds 27 and 31 were more potent than those of the 4-methoxy (26), 5-ethoxy (29 and 33), 5difluoromethoxy (28 and 32), 5-isopropoxy (34), and 1,3dioxolane (30 and 35)-substituted analogues, suggesting that the 5-methoxy group on the indole ring was favorable for improving the antitumor activity. In addition, the replacement of the central scaffold of 11H-indolo [3,2-c]isoquinoline (35) by 6,11-dihydro-5H-indolo [3,2-c]isoquinolin-5-one (24) generates less-potent products, and the 1-chlorine substitution on the isoquinoline ring (27) decreases the antiproliferative activity of the compound (31). Among them, compound 31 represents the optimal agent, with IC 50 values of 0.53 μM against the HCT116 cancer cell line, and showed from 3.8-to In addition, the antitumor activities of the heterocyclicsubstituted indolo [3,2-c]isoquinoline derivatives were investigated (Table 3).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The treatment of 2-methoxy-3-(2-nitrophenyl)-1-oxo-1,2,3,4-tetrahydroisoquinoline-4-carboxylic acid ( 146 ) with sodium sulfide yields 147 , which is further transformed to indolo[3,2- c ]isoquinoline ( 148 ). On the other hand, the reduction of 146 with ammonium formate produces 149 which by cyclisation and dehydrogenation yields dibenzo[ c , h ][1,6]naphthyridine ( 150 ; Scheme 47 ) [ 87 ].…”
Section: Two-component Castagnoli–cushman Reactions (2c-ccr)mentioning
confidence: 99%